Role of farmers in setting breeding goals - Subedi, Madu; Shrestha, P.K.; Sunwar, Sharmila; Subedi, A. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Maize (Zea mays L.) is the most important crop in the hill farming system in Nepal. It plays an important role in the livelihood of the people living in the hills. The hilly area of the Palpa, Gulmi, and Arghakhanchi districts extending towards Pyuthan and further west has a unique geophysical environment, which is different from other maize-growing areas in Nepal. Farmers in this area not only have poor access to agricultural inputs, including improved genetic materials, but the improved varieties tested so far do not exactly match the unique growing conditions and the needs of farmers in the area. Therefore, the major proportion of maize in the Palpa, Gulmi, and Arghakhanchi districts is dominated by local varieties. Several factors are responsible for low productivity and for other associated problems of maize production in the area.